2018
DOI: 10.1007/s00228-018-2427-3
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and pharmacodynamics of ticagrelor and AR-C124910XX in Chinese healthy male subjects

Abstract: Our study developed a population PK-PD model for ticagrelor and further simulation for dosage regimen was performed based on the final model. Compared to the current recommended dosage regimen (180 mg LD, 90 mg MD), our simulation result of a relatively lower dose (30 mg MD) could also obtain an acceptable anti-platelet response, which may provide a reference for further dosage regimen design in Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Data from a clinical trial further corroborated the finding that the CYP3A4*22 allele impaired the elimination and increased the exposure of ticagrelor in healthy Finnish volunteers of Caucasian ethnicity (Holmberg et al, 2019). Furthermore, the CYP3A4*1G allele also increased the clearance of its active metabolite, AR-C124910XX, and had no effect on the PK of ticagrelor in healthy Chinese volunteers (Liu et al, 2018). Moreover, genetic variants of SLCO1B1 rs113681054, SLCO1B1*5 (rs4149056), and CYP3A5*3 (rs776746) were also reported to have no relevance in the PK of ticagrelor in healthy Chinese volunteers (Li et al, 2017a).…”
Section: Introductionsupporting
confidence: 52%
“…Data from a clinical trial further corroborated the finding that the CYP3A4*22 allele impaired the elimination and increased the exposure of ticagrelor in healthy Finnish volunteers of Caucasian ethnicity (Holmberg et al, 2019). Furthermore, the CYP3A4*1G allele also increased the clearance of its active metabolite, AR-C124910XX, and had no effect on the PK of ticagrelor in healthy Chinese volunteers (Liu et al, 2018). Moreover, genetic variants of SLCO1B1 rs113681054, SLCO1B1*5 (rs4149056), and CYP3A5*3 (rs776746) were also reported to have no relevance in the PK of ticagrelor in healthy Chinese volunteers (Li et al, 2017a).…”
Section: Introductionsupporting
confidence: 52%
“…The EC50 for TAM is much lower at 98.5 nmol/L. The model presented here is different from others in literature 14,18 where the relationship is either modeled as a sum of TICA and TAM or just TICA alone. The model presented here fits the placebo data (subjects who received TICA plus a placebo) well, suggesting that the model here performs as well as those used elsewhere.…”
Section: Discussionmentioning
confidence: 62%
“…Because ticagrelor is a substrate of P‐glycoprotein (P‐gp), the levels of which are higher in men than in women, it is speculated that the effect of ticagrelor on metabolite clearance may be related to sex differences. Few factors influence the PKs of ticagrelor, and the most common ones that have been reported are gender and age as significant covariates in PopPK models of ticagrelor and AR‐C124910XX 17,27 . Among them, the PopPK model of ticagrelor developed by Li et al 28 .…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Liu et al reported that the serum levels of ticagrelor correlate with the bleeding risk in Chinese patients. 17 Thus, adjusting the ticagrelor dose in Chinese patients with ACS might be a potential way to reduce the risk of bleeding in these patients.…”
Section: Articlementioning
confidence: 99%